2018
DOI: 10.1038/s41419-018-1076-x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of furin increases epileptic susceptibility

Abstract: The proprotein convertase Furin plays crucial roles in the pathology of many diseases. However, the specific role of furin in epilepsy remains unclear. In our study, furin protein was increased in the temporal neocortex of epileptic patients and in the hippocampus and cortex of epileptic mice. The furin transgenic (TG) mice showed increased susceptibility to epilepsy and heightened epileptic activity compared with wild-type (WT) mice. Conversely, lentivirus-mediated knockdown of furin restrained epileptic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…Furin and other PCs process a large number of precursor proteins, such as hormones, neuropeptides, growth factors and their receptors, bacterial toxins, and adhesion molecule, through various secretory pathways (Seidah and Prat, 2012). Thus, the deregulation of FURIN is correlated with a variety of pathological conditions, including cardiovascular disease (Yakala et al, 2019), rheumatoid disease (Valli et al, 2019), endocrinopathies (Al Rifai et al, 2017), and central nervous system disorder (Yang et al, 2018). As for cancers, several studies have found that FURIN is expressed in various cancers and sarcomas (Khatib et al, 2002;Coppola et al, 2008;Lee et al, 2016;Jaaks and Bernasconi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furin and other PCs process a large number of precursor proteins, such as hormones, neuropeptides, growth factors and their receptors, bacterial toxins, and adhesion molecule, through various secretory pathways (Seidah and Prat, 2012). Thus, the deregulation of FURIN is correlated with a variety of pathological conditions, including cardiovascular disease (Yakala et al, 2019), rheumatoid disease (Valli et al, 2019), endocrinopathies (Al Rifai et al, 2017), and central nervous system disorder (Yang et al, 2018). As for cancers, several studies have found that FURIN is expressed in various cancers and sarcomas (Khatib et al, 2002;Coppola et al, 2008;Lee et al, 2016;Jaaks and Bernasconi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The method of sIPSCs recording was as same as mIPSCs without adding TTX in ACSF. sIPSCs were recorded in the present of gabazine (SR95531) (0.5 μ m ) or picrotoxin (10 μ m ) in ACSF 20 . eIPSCs were collected in the present of DNQX (20 μ m ) and APV (40 μ m ) at a holding potential of − 70 mV.…”
Section: Methodsmentioning
confidence: 99%
“…The mice in the PTZ-kindled model were intraperitoneally injected with a daily subconvulsive dose of PTZ (35 mg/kg, Sigma-Aldrich, USA) between 9:00 AM and 11:00 AM. 13,14 The rest mice were assigned as controls and were injected with the corresponding dose of saline solution. The intensity of seizure was evaluated on the basis of Racine's scale evaluation 13 : 1: mouse and facial movements; 2: head nodding; 3: forelimb clonus; 4: rearing; and 5: rearing and falling.…”
Section: Ptz-kindled Mouse Modelmentioning
confidence: 99%
“…Cultures of hippocampal neurons were prepared from postnatal day 0 C57BL/6J pups of either sex as mentioned. 14,15 Neurons were plated in DMEM containing 10% fetal bovine serum (FBS) (Scitecher, French), 1% penicillin-streptomycin (P/S) (Gibco, USA), and 1% lglutamine (Gbico, Brazil). Four to six hours later, the culture medium was exchanged completely with the neurobasal medium containing 2% B27 supplement (Gbico, USA), 1% P/S, and 1% l-glutamine.…”
Section: Neuronal Culture Preparation Dna Constructs and Transfectionmentioning
confidence: 99%